EDUKASI PANGAN SUMBER PROTEIN BAGI ANAK DENGAN MEDIA PERMAINAN MONOPOLI - Alfrida Aisyah Masyhudi (LENTERA: JOURNAL OF GENDER AND CHILDREN STUDIES, 2020)
Integrative thematic learning requires teachers create an atmosphere of active and innovative learning. The objectives of this study include; (1) making monopolies game media as a source of learning on the theme of my healthy and nutritious food about protein food sources, (2) knowing the effectiveness of the media and the influence of cognitive, affective aspects, and (3) knowing students' responses to monopoly game media developed. The development of monopoly media uses the ADDIE model (analysis, design, development, implementation, and evaluation). Data collection uses observation, written test and questionnaire. Sources of data collected in the form of quantitative data which is then analyzed descriptively. Techniques of data analysis using different T-test. The results showed that the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) that was used in the process of developing a monopoly game media for protein food sources included game media, the material presented, and overall learning tools obtained excellent results. . In addition, there was an increase in the aspects of cognitive abilities of students with an average value obtained that is 84 of the average value obtained before the application of monopoly game media that is 51.5, aspects of the affective ability of students gained a value of 88.25% including in the criteria of very good or greatly improved, and students' responses gained a value of 88.25% included in the criteria is very good.